Multiple Drug Resistant Streptococcus Strains-An Actual Problem in Pig Farms in Western Romania - Luminita Costinar; Corina Badea; Adela Marcu; Corina Pascu; Viorel Herman (MDPI AG, 2024)
Streptococci are a type of bacteria that can cause severe illnesses in humans and animals. Some typical species like S. suis, or atypical species like S. porcinus and, S. dysgalactiae subsp. dysgalactiae, can cause infections like septicemia, meningitis, endocarditis, arthritis, and septic shock. S. suis is considered a newly emerging zoonotic pathogen. Although human streptococcal infection outbreaks are rare, it is appropriate to review the main streptococcal species isolated in pig farms in western Romania, due to the high degree of antibiotic resistance among most isolates commonly used in human treatment. This study examines the resistance patterns of these isolates over 5 years (2018-2023). The research investigated the antimicrobial susceptibility of 267 strains of Streptococcus spp. isolated from pigs, primarily from lung and brain tissues. This report is the first to describe the distribution of atypical Streptococcus species (SDSE, S. porcinus, S. hyovaginalis, S. pluranimalium, S. canis) in Romania, as well as the antibiotic resistance profile of these potentially zoonotic species. It is important to re-evaluate and consider the high rates of resistance of S. suis to tetracyclines, lincosamides, macrolides, and aminoglycosides, as well as the high recovery rates of S. suis from the lungs and brain when treating swine diseases.